TINJAUAN YURIDIS TERHADAP IMPLEMENTASI PIDANA MATI BAGI PELAKU TINDAK PIDANA PEMBUNUHAN BERENCANA - Buulolo, Balasius Basozisekhi (Jurnal Panah Hukum, 2025)
The death penalty is the imposition of a crime by depriving an individual who has broken a law that stipulates that their offense is punished by death of their right to life. To get the death penalty is to take someone's life. Severe crimes will carry the death sentence; premeditated murder is one such offense that was tried by a panel of judges at the Sengeti District Court (Decision Number: 36/Pid.B/2013/PN.Snt). In this ruling, the judge determined that the defendant had been shown legally and credibly guilty of premeditated murder. imposed the death punishment on the accused. The study is titled "Judicial review of the application of capital punishment for premeditated murderers" (Decision Study Number). Normative legal research employing the statutory approach, case approach, and analytical method is the sort of study that is done. Primary, secondary, and tertiary data were used in the data gathering process. Deductive reasoning is employed to arrive at conclusions from the descriptive qualitative data analysis. Drawing on study findings and debates, it may be determined that the judges' decision to impose the death penalty was motivated by retaliation rather than serving as a deterrence for the offender. According to researchers, the application of the death sentence for those who commit premeditated murder violates both Article 9 paragraph (1) and Article 28 A of the 1945 Constitution from a legal standpoint.